The Development of School Culture Based on Local Cultural Values in Elementary Schools of Central Aceh Regency - Hariki Fitrah; Sumanti; Hamsidar HS; Eviana Sonata (Academy of Education Journal, 2026)
This research investigates the development of school culture grounded in local wisdom at SD Negeri 12 Kute Panang, Central Aceh Regency. The study adopts a qualitative design with a descriptive approach. Data sources comprise primary data collected directly from field informants and secondary data obtained from relevant school documents. The participants include the principal, teachers, students, and community members. Data collection methods involve observation, interviews, and documentation, while analysis is conducted through data reduction, data display, and conclusion drawing/verification. The results reveal several school activities that reflect the application of local wisdom values, which also serve as integral components of the school’s culture. These include: (1) Cultivation of Gayo coffee, a prominent regional commodity and a primary source of income for local residents. At school, students receive guidance from teachers on coffee farming techniques, from seedling preparation to post-harvest processing—providing both practical knowledge and character-building experiences. (2) Traditional arts, such as Didong and Tari Guel, which hold deep cultural meaning for the Gayo community. At SD Negeri 12 Kute Panang, these activities are conducted on Thursdays, with students organized into groups and trained by teachers. (3) Traditional cuisine, where students are introduced to local specialties including gutel, masam jing, and lepat.